OPTIMIZATION OF DIAGNOSTIC IMAGING IN BREAST CANCER - S. A. Velichko; Yu. I. Tyukalov; I. G. Frolova; D. G. Bukharin; Ye. Ye. Bober (Бюллетень сибирской медицины, 2015)
The paper presents the results of breast imaging for 47200 women. Breast cancer was detected in 862 (1.9%) patients, fibroadenoma in 1267 (2.7%) patients and isolated breast cysts in 1162 (2.4%) patients. Different types of fibrocystic breast disease (adenosis, diffuse fibrocystic changes, local fibrosis and others) were observed in 60.1% of women. Problems of breast cancer visualization during mammography, characterized by the appearance of fibrocystic mastopathy (sclerosing adenosis, fibrous bands along the ducts) have been analyzed. Data on the development of diagnostic algorithms including the modern techniques for ultrasound and interventional radiology aimed at detecting early breast cancer have been presented.